TRACKING SUN PATH AND VOLTAGE MONITORING SYSTEM - N.Jyothsna; Lasya Priya Bhavanchikar; B.Bhavani; K. Vyshnavi; K.Pratyusha (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Presently we are invading in a new period of modernisms i.e., Internet of Things (IoT). By using the IoT supervising solar energy can greatly enhance the performance, monitoring of the plant. It is a technique to keep track of the dust assembled on the solar panels to induce the maximum power for active utilization. The amount of output power of the solar panels depends on the radiation hit to the solar cell. All the panels are attached and the sensors are precisely connected to the central controller which supervise the panels and loads. Thus, user can view the current, voltage and sunlight.